Authentic Christianity : the classic bestseller on living the life of faith with integrity - Stedman, Ray C., 1917-1992 (Discovery House Publishers ; Distributed to the trade by Thomas Nelson Publishers, 1996)
This classic by Ray Stedman moves you beyond religion, doctrine, rules, and rituals into the life-changing experience of being genuinely and intimately connected with Christ. He shows you how to live a life of faith with integrity - a life that attracts people and compels them to seek its Source.